Accuracy of transient elastography in assessing liver fibrosis in chronic viral hepatitis: A multicentre, retrospective study. (26th February 2015) - Seo, Yeon Seok; Kim, Moon Young; Kim, Seung Up; Hyun, Bae Si; Jang, Jae Young; Lee, Jin Woo; Lee, Jung Il; Suh, Sang Jun; Park, Soo Young; Park, Hana; Jung, Eun Uk; Kim, Byung Seok; et al.
Abstract Background/Aims Transient elastography (TE) has become an alternative to liver biopsy (LB). This study investigated the diagnostic performance of liver stiffness (LS) measurement using TE in Korean patients with chronic hepatitis B and C (CHB and CHC). Methods From April 2006 to June 2014, 916 patients (567 CHB and 349 CHC) who underwent LB and TE at 15 centres were analyzed. The Batts and Ludwig scoring system was used for histologic assessment. Aspartate aminotransferase (AST)–to–platelet ratio indexes (APRI) were calculated. Area under the receiver operating characteristic curve (AUROC) was used. Results The median age, LS value, and APRI score were 45 years, 8.8 kPa, and 0.61, respectively, in CHB patients vs. 51 years, 6.8 kPa and 0.55, respectively, in CHC patients. TE was significantly superior to APRI in CHB patients (AUROC 0.774 vs. 0.72 for ≥F2, 0.849 vs. 0.812 for ≥F3, and 0.902 vs. 0.707 for F4, respectively; all P < 0.05). Furthermore, TE was significantly superior for predicting ≥ F3 stage (AUROC 0.865 vs. 0.840, P = 0.009) whereas it was similar for predicting ≥ F2 and F4 stage (AUROC 0.822 vs. 0.796; 0.910 vs. 0.884; all P > 0.05) in CHC patients. In CHB patients, optimal cut‐off LS values were 7.8 kPa for ≥F2, 8.2 kPa for ≥ F3, and 11.6 kPa for F4, vs. 6.8 kPa, 8.6 kPa, and 14.5 kPa, respectively, in CHC patients. Conclusions TE can accurately assess the degree of liver fibrosis in Korean patients with CVH. TE was superior to APRI for predicting each fibrosis stage.